Respuesta :
The slope intercept of a line is given by y=mx+c, where:
m=slope, c=y-intercept.
Thus the slope-intercept form of our equation will be:
-6+2y≤42
adding 6 in both sides we get:
-6+6+2y≤42+6
2y≤6
dividing both sides by 2 we get:
(2y)/2≤6/2
y≤3
the answer is y≤3
m=slope, c=y-intercept.
Thus the slope-intercept form of our equation will be:
-6+2y≤42
adding 6 in both sides we get:
-6+6+2y≤42+6
2y≤6
dividing both sides by 2 we get:
(2y)/2≤6/2
y≤3
the answer is y≤3
Answer: The required slpe-intercept form of the given inequality is
[tex]y\leq 0\times x+24.[/tex]
Step-by-step explanation: We are given to write the following inequality in the slope-intercept form :
[tex]-6+2y\leq 42~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We know that
the slope intercept form of a straight line with slope m and y-intercept c is given by
[tex]y=mx+c.[/tex]
Writing equation (i) in slope-intercept form, we have
[tex]-6+2y\leq 42\\\\\Rightarrow 2y\leq 42+6\\\\\Rightarrow 2y\leq 48\\\\\Rightarrow y\leq 24\\\\\Rightarrow y\leq 0\times x+24,[/tex]
where slope, m = 0 and y-intercept, c = 24.
Thus, the required slpe-intercept form of the given inequality is
[tex]y\leq 0\times x+24.[/tex]